HUMAN-CENTERED DESIGN UNTUK PERANCANGAN MEDIA REHABILITASI PASCA STROKE BERBASIS AUDIO VISUAL - Danis Rifa Nurqotimah; Ahsanun Naseh Khudori; Risqy Siwi Pradini (Yayasan Nusantara Hasana Berdikari, 2024)
Stroke is a condition that makes a person's whole body or part of his body paralyzed. The leading cause of death and disability in the world is Stroke. Each year, there are more than 12.2 million new Stroke cases, and more than 101 million people with this condition. With proper care and prompt therapy, Stroke patients can recover. The study aims to design visual media for post-Stroke rehabilitation. The method applied in this research is a combination of ISO 9241-210:2019 Human-Centered Design, persona, and expert validation. The stages of designing audio visual media consist of pre-production, production and editing. Finally, this study produces audio-visual media for post-Stroke rehabilitation that has been validated by experts.